Effect of factors on growth and development of Dendrobium officinale Kimura et Migo cultured in vitro and ex vitro - Luan, Vu Quoc; Tung, Hoang Thanh; Hien, Vu Thi; Khai, Hoang Dac; Cuong, Do Manh; Huong, Trinh Thi; Vinh, Bui Van The; Tu, Vu Thi; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2021)
Dendrobium officinate Kimura et Migo, a species of orchid for beautiful flowers, is used in traditional medicine in many Asian countries because there are many important pharmaceuticals (chrysotoxene, erianin, confusarin, polysaccharide, alkaloid ...) in anti-cancer, anti-aging, boosting immunity and vasodilation, etc. In recent years, more than 4,000 hectares of Dendrobium officinate Kimura et Migo artificial planting has been available in China and the price of dry product was around ¥ 80,000/kg. Currently, plantlet quality is an important factor influencing the acclimatization stage, growth, and development of plants in the greenhouse. In this study, the effect of a number of factors medium, plant regulator, ventilation, and substrate to improve plantlet quality as well as further growth and development in the greenhouse conditions were investigated. The results showed that SH medium was suitable for in vitro shoot growth in terms of monitoring parameters after 90 days of culture. In shoot multiplication stage, the shoots culture on SH medium supplemented with 2 mg/L BA, 30 g/L sucrose, 9 g/L agar, 1g /L activated charcoal (AC) gave the best results with 4.53 shoots/per shoot. The SH medium supplemented with 1.0 mg/L NAA, 30 g/L sucrose, 9 g/L agar, 1.0 g/L AC combined with ventilation conditions was suitable for rooting stage with plant height (5.73 cm), number of roots (4.77), root length (5.00 cm), fresh weight (3.36 g), dry weight (0,31 g), and total chlorophyll (SPAD) (45.76 nmol/cm2). Plantlets derived from culture ventilation conditions cultivated on the mixture of pine bark and fern fiber (50:50) was the highest survival rate (100%) and growth after 12 months in the greenhouse.